INVENTARISASI DAERAH RAWAN LONGSOR KABUPATEN BANJARNEGARA JAWA TENGAH - Warnadi Warnadi (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2014)
ABSTRACT This Research aims to inventory landslide-prone areas in Banjarnegara district, Central Java. The study was conducted between May-September 2012. The method used in this research is descriptive quantitative method with a spatial approach. Technical analysis of the data in this study is the use overlay of several variables landslides, the data is then entered into the data input software program Arc View. The data is processed, then is the determination of landslide prone areas using Storie index Broadly speaking causative factor.a landslides) geological conditions such as weathered rock, soil layers slope, earthquakes and volcanic eruptions.b) Climate namely when high rainfall .c) topography is steep slopes. Pagenten subdistricts and districts Pandanarum including the high risk of avalanche danger. This can be evidenced by the number of landslides that often occur, particularly in the village of Tlaga (Pandanarum district) and Mundasari village and village in the district Suwidak Pagenten. Subdistrict Wanayasa, Batur, Banjarmangu, Kalibening and Sigaluh is a district that includes categorized as being the average of 4-6 landslide each year. Region of relatively light among other avalanche events in the Pejawaran district , Banjarnegara, Pagedongan, Lampok, and Purwanegara with only 2-4 landslide each year. Keywords: Inventory landslide-prone areas, Banjarnegara, Central Java.